Alternative HPV vaccination schedules in Latin America - Claudia Robles; María de la Luz Hernández; Maribel Almonte (Instituto Nacional de Salud Pública, 2018)
In 2008, the first HPV vaccination program in Latin America started in Panama, targeting girls aged 10-11 years with a 3-dose vaccine schedule, an initiative that was to be followed by other Latin American countries after local feasibility and population acceptability evaluations were completed. A 3-dose vaccine regimen over six months was originally chosen for HPV vaccines, copying the Hepatitis B vaccine schedule (0, 1-2, 6 months). Alternative vaccine schedules have been proposed afterwards based on: i) noninferior immunogenicity or immune response levels compared to those at which clinical efficacy has been proven (i.e., those observed in a 3-dose HPV vaccine schedule in women aged 15-26), and, ii) proven efficacy in clinical trials and/or effectiveness among women who were provided less than three doses due to a lack of adherence to a 3-dose vaccine schedule. In 2014, based on the available evidence and the potential increase in coverage by expansion of vaccination target groups, particularly in low and middle income countries (LMIC), the World Health Organization recommended a 2-dose schedule with at least a 6-month interval between doses for females up to 15 years of age and a 3-dose schedule for older women. More recently, it has been suggested that 1-dose HPV vaccination schemes may provide enough protection against HPV infection and may speed up the introduction of HPV vaccination in LMIC, where most needed.